Modelling cerebrovascular pathology and the spread of amyloid beta in Alzheimer’s disease - Ahern, A; Thompson, TB; Oliveri, H; Lorthois, S; Goriely, A (Royal Society, 2025)
Alzheimer’s disease is characterised by the accumulation and spread of the amyloid beta protein in the brain. Experiments have revealed that amyloid beta oligomers induce microvascular mural cells to contract, thereby constricting capillaries and increasing resistance to blood flow. Conversely, hypoperfusion promotes amyloid beta production and hinders its clearance, hence creating a pathogenic positive feedback loop. Here, we develop a brain-wide model that combines protein-capillary interactions with the prion-like dynamics of amyloid beta in the structural connectome. We find that a bistable dynamics emerges from the amyloid betahypoperfusion feedback loop giving rise to nontrivial spatio-temporal dynamics. Through mathematical and computational analyses, we uncover several new biologically-relevant threshold phenomena with implications for disease initiation and spreading. In particular, we describe how a deficit in arterial blood supply can trigger disease outbreak, consistent with the two-hit vascular hypothesis of Alzheimer’s disease.